2012
DOI: 10.1093/treephys/tps005
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of elevated ozone and temperature on carbon allocation of silver birch (Betula pendula) genotypes in an open-air field exposure

Abstract: In the present experiment, the single and combined effects of elevated temperature and ozone (O(3)) on four silver birch genotypes (gt12, gt14, gt15 and gt25) were studied in an open-air field exposure design. Above- and below-ground biomass accumulation, stem growth and soil respiration were measured in 2008. In addition, a (13)C-labelling experiment was conducted with gt15 trees. After the second exposure season, elevated temperature increased silver birch above- and below-ground growth and soil respiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Binkley et al 2010). The length of the growing period of silver birch is genetically determined and strongly connected to the height growth (Rousi and Pusenius 2005), and it has been shown that there is large within population genetic variation in birch's acclimation to changing climate (Kasurinen et al 2012). Breeding silver birch genotypes for better growth in Canadian conditions should thus be a very profitable approach and worth further consideration.…”
Section: Silver Birch As a Commercial Or Ornamental Species In Canadamentioning
confidence: 99%
“…Binkley et al 2010). The length of the growing period of silver birch is genetically determined and strongly connected to the height growth (Rousi and Pusenius 2005), and it has been shown that there is large within population genetic variation in birch's acclimation to changing climate (Kasurinen et al 2012). Breeding silver birch genotypes for better growth in Canadian conditions should thus be a very profitable approach and worth further consideration.…”
Section: Silver Birch As a Commercial Or Ornamental Species In Canadamentioning
confidence: 99%
“…It has been reported that stomatal regulation, efficiency in reactive oxygen species (ROS) scavenging and accumulation of key proteins are crucial plant responses to survive this stress combination (Zandalinas et al , , Balfagón et al ). Furthermore, combination of high temperatures and ozone stress had a negative effect on Betula pendula growth and leaf biomass production because allocation of carbon is partly altered by ozone stress (Kasurinen et al ). Also, it has been described that aldehyde dehydrogenase enzymes, which contribute to redox balance by producing NADPH and NADH, are key in Arabidopsis thaliana (Arabidopsis) survival under combination of wounding and heat stress (Zhao et al ).…”
Section: Introductionmentioning
confidence: 99%
“…For example the following two topics have received little attention: Climate change has been found to affect various crop species differently (e.g., Feng and Kobayashi, 2009;Kimball, 1986;Luo, 2011;Mills et al, 2007), however, the intraspecific variation -between and within accessions -in response to changes has received little focus (e.g., Craufurd et al, 2003;Pleijel, 2011;Weigel and Manderscheid, 2012). Also, in studies of climate change effects on crop accessions, rather few have investigated the effects of treatments, where more than one climate factor was changed (Alemayehu et al, 2014;Clausen et al, 2011;Frenck et al, 2011;Juknys et al, 2011;Kasurinen et al, 2012;Mitchell et al, 1993;Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%